Pemupukan sebagai Penentu Produktivitas Ubi Jalar - Paturohman, Eman; Sumarno, Sumarno (Buletin Iptek Tanaman Pangan, 2015)
Sweet potato (Ipomoea batatas L.) is a cosmopolitan crop, grown on 116 countries in the world. A total of 34 countries harvested 200,000 tons or more fresh tuber annually, and 82 countries with a national production less than 200,000 tons per year. China accounted for 68% of the worldâs sweet potato production or 90% of the Asian fresh tuber production. The sweet potato productivity varies among countries in the world, from less than 5 t/ha to 24 t/ha, mainly related to the amount use of inorganic fertilizers of N, K, and organic fertilizer. The recommended use of fertilizers for sweet potato is as follow: low to moderate dosage of N (40 to 75 kg N/ha), low dossage of P (20-50 kg P2O5 /ha), and medium to high dosage of K (75-100 kg K2O/ha), combined with organic manure (3-10 t/ha). Indonesian sweet potato productivity is relatively high as compared to that in other countries in the world with an average of 14.75 t/ha. In the provincial production center, sweet potato productivity ranges from 18 to 22.7 t/ha fresh tuber except in Nusa Tenggara Timur (7.5 t/ha) and Papua (10.9 t/ha). In other provinces, the productivities range from 7.1 to 15.5 t/ha fresh tubers. Commercial sweet potato farming is always carried out under an optimum agroecology condition; however farmers do not always obtain optimum yield due to inoptimum application of fertilizer. Application of the recommended dosage of inorganic fertilizers with the addition of 3 to 5 t/ha organic manure is expected to improve sweet potato productivity to 24-25 t/ha fresh tubers. Improvement on sweet potato productivity will increase the supply of fresh tubers to the markets and thus, increases the sweet potato consumption as a rice substitute.